Cutaneous eyelid tuberculosis – a case report - Wyrwicka, Anna; Minias, Radosław; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Tuberculosis is a bacterial infection caused by a germ called Mycobacterium tuberculosis. The bacteria usually attacks the lungs, but it can also affects other human organs or tissues. Localization of tuberculosis out of respiratory system is very rare and sometimes difficult to establish. Our patient finally diagnosed as lid tuberculosis with negative tuberculin reaction and clinical presentation as basal cell carcinoma of the lids, is a strong argument for that.